Utility of Intraoperative Ultrasound in Neurosurgery - Faria Méndez, Gustavo Enrique; Roa Chacón, César José; Brito Núñez, Nafxiel Jesus; Zerpa, José Ramón (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Objective The purpose of the present study is to demonstrate the usefulness of intraoperative ultrasound guidance as a technique for the assessment, in real time, of tumor resection and as a navigation aid during intra-axial brain lesion removal on patients admitted in the Neurosurgical Department at the Hospital Universitario de Caracas, Caracas, Venezuela, in 2018.Methods A total of 10 patients were enrolled, each with intra-axial brain lesions with no previous neurosurgical procedures and a mean age of 49 years old, ranging from 29 to 59 years old.Results A male predominance was observed with 7 cases (70%) over 3 female cases (30%). Six patients had lesions in the dominant hemisphere. The frontal lobe was the most commonly affected, with 5 cases, followed by the parietal lobe, with 4 cases. After craniotomy, ultrasound evaluation was performed previously to dural opening, during tumor resection and after tumor removal. The mean tumor size in axial, coronal and sagittal views was 3.72 cm, 3.08 cm and 3.00 cm, respectively, previously to dural opening with intraoperative ultrasound. The average tumor depth was 1.73 cm from the cerebral cortex. The location and removal duration from the beginning of the approach (ultrasound usage time) was 83.60 minutes, and the average surgery duration was 201 minutes. Navigation with intraoperative ultrasound served to resect intra-axial tumors more precisely and safely. There was no postoperative complication associated with the surgery in this series of cases.Conclusions Intraoperative ultrasound guidance for intra-axial subcortical tumor resection is a technique that serves as a surgical and anatomical orientation tool.
Keywords: intraoperative ultrasound; brain tumor; glioma surgery